Perspective: Zinc‐Tin Oxide Based Memristors for Sustainable and Flexible In‐Memory Computing Edge Devices - Carlos Silva; Jonas Deuermeier; Weidong Zhang; Emanuel Carlos; Pedro Barquinha; Rodrigo Martins; Asal Kiazadeh (Advanced Electronic Materials, 2023)
Abstract As the Internet of things (IOT) industry continues to grow with an ever‐increasing number of connected devices, the need for processing large amounts of data in a fast and energy‐efficient way becomes an even more pressing issue. Alternative computation devices such as resistive random access memories (RRAM), or memristors, started taking centre stage as prime candidates to tackle this issue due to their in‐memory computation capabilities. Amorphous oxide semiconductors (AOSs), more specifically eco‐friendly zinc‐tin oxide (ZTO), show great promise as a memristive active material for flexible and sustainable applications due to its low required fabrication temperature, amorphous structure, low‐cost, and critical‐raw‐material‐free composition. In this perspective article, the research progress on ZTO‐based memristors is reviewed in terms of device structure and material compositions. The effects on the electrical performance of the devices are studied. Additionally, neuromorphic and optoelectronic capabilities are analyzed with the objective of finding the best approaches toward implementing these devices in novel computing paradigms.